Porositas Beton High Volume Fly Ash (Hvfa) Di Air Gambut - Ika Qoriah Nursuci; Ismeddiyanto Ismeddiyanto; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to examine the porosity of concrete with the use of fly ash as a substitute for a large portion of cement (HVFA). Ordinary Portland Cement (OPC) specimen is used as a control of HVFA concrete. The content of pozzolanic material in HVFA concrete is 45% of fly ash. Fly Ash (FA) contained in HVFA concrete in this study had a variation of 50% by weight of cement. After the concrete was released from the mold, OPC and HVFA concrete was cured by soaking it normal water for 28 days. Then, the specimen is was removed and soaked again in peat water for ages 7 and 28 days. When concrete reached their respective ages, porosity testing was carried out on concrete. The results shared that the porosity of OPC immensed in peat water was 17.35% higher than that of immensed in normal water. The increase of porosity on OPC specimen was do the attack of acid contained in peat water which made the specimen became porous and increased its porosity value. On the other hand, HVFA specimen was more resistant to peat water. This was indicated by a decrease in the porosity value of 19.83%. HVFA specimen contained large amounts of FA, the pozzolanic FA makes concrete more resistant to the peat environment and neutralizes the impact of peat on specimen. Keywords: Porosity, fly ash (fly ash), HVFA, peat water.